Amino acids and mammary gland development: nutritional implications for milk production and neonatal growth. Issue 1 (December 2016) - Rezaei, Reza; Wu, Zhenlong; Hou, Yongqing; Bazer, Fuller; Wu, Guoyao
Abstract Milk is synthesized by mammary epithelial cells of lactating mammals. The synthetic capacity of the mammary gland depends largely on the number and efficiency of functional mammary epithelial cells. Structural development of the mammary gland occurs during fetal growth, prepubertal and post-pubertal periods, pregnancy, and lactation under the control of various hormones (particularly estrogen, growth hormone, insulin-like growth factor-I, progesterone, placental lactogen, and prolactin) in a species- and stage-dependent manner. Milk is essential for the growth, development, and health of neonates. Amino acids (AA), present in both free and peptide-bound forms, are the most abundant organic nutrients in the milk of farm animals. Uptake of AA from the arterial blood of the lactating dam is the ultimate source of proteins (primarily β-casein and α-lactalbumin) and bioactive nitrogenous metabolites in milk. Results of recent studies indicate extensive catabolism of branched-chain AA (leucine, isoleucine and valine) and arginine to synthesize glutamate, glutamine, alanine, aspartate, asparagine, proline, and polyamines. The formation of polypeptides from AA is regulated not only by hormones (e.g., prolactin, insulin and glucocorticoids) and the rate of blood flow across the lactating mammary gland, but also by concentrations of AA, lipids, glucose, vitamins and minerals in the maternal plasma, as well as the activation of the mechanistic (mammalian) target rapamycin signaling by certain AA (e.g., arginine, branched-chain AA, and glutamine). Knowledge of AA utilization (including metabolism) by mammary epithelial cells will enhance our fundamental understanding of lactation biology and has important implications for improving the efficiency of livestock production worldwide.